Altered ribostasis: RNA-protein granules in degenerative disorders - RAMASWAMI, MANI (My University, 2013)
The molecular processes that contribute to degenerative diseases are not well understood. Recent observations suggest that some degenerative diseases are promoted by the accumulation of nuclear or cytoplasmic RNA-protein (RNP) aggregates, which can be related to endogenous RNP granules. RNP aggregates arise commonly in degenerative diseases because RNA-binding proteins commonly self-assemble, in part through prion-like domains, which can form self-propagating amyloids. RNP aggregates may be toxic due to multiple perturbations of posttranscriptional control, thereby disrupting the normal "ribostasis" of the cell. This suggests that understanding and modulating RNP assembly or clearance may be effective approaches to developing therapies for these diseases.
PUBLISHED
Keywords: Genetics